Research Misconduct Sebagai Suatu Tindak Pidana Penyebaran Berita Bohong: Sebuah Tinjauan Hukum Pidana - Royadi, Kemal Fikri; Harissa, Monte Carlo Faza (UI Scholars Hub, 2025)
Research is one of the gates to uncover wisdom in scientific disciplines. In its implementation, it is often found that there are various interests underlying the research. These various interests also have their own purpose to the extent that it can influence the results of the research which can have implications to form a research misconduct. This research aims to review the national criminal law regarding this behavior by examining the relevant act’s articles as well as scholarly dogmatics due to the absence of laws regulating this matter. The method used in this research is juridical-normative using conceptual approach and literature research in order to collect the data. The results of this research are that by extensively interpreting the elements of articles regarding fake news crime, research misconduct that causes disturbance can be punished. This can fill the legal void regarding the prosecution of research misconduct even though it can only be implemented starting in 2026. Hence the national criminal law still accommodates punishment for research misconduct.